Pregnancy's health in the context of emergency in public health: reflections of the COVID-19 pandemic (Research, Society and Development, 2022)
This is a study of theoretical reflection that aimed to present the repercussions of the Coronavirus on the health of pregnant women and discuss the repercussions of the COVID-19 pandemic on health care for this population, based on the recommendations proposed by the World Health Organization. Therefore, it presents a systematic reflection and discussion around two main axes: 1) Pregnant women and COVID-19” and 2) Attention to the health of pregnant women in the pandemic. Understanding the essentiality of planning and organizing health services at the various levels of health care is of paramount importance for coping with the pandemic and for promoting comprehensive care for pregnant women, especially in health emergency contexts.